2015
DOI: 10.1186/s12935-015-0200-6
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance characterization in multicellular tumour spheroids from two human lung cancer cell lines

Abstract: BackgroundMost of the knowledge about the mechanisms of multidrug resistance in lung cancer has been achieved through the use of cell lines isolated from tumours cultivated either in suspensions of isolated cells or in monolayers and following exposition to different cytostatic agents. However, tumour cell lines growing as multicellular tumour spheroids (MTS) frequently develop multicellular resistance in a drug-independent form. The aim of this study was to characterize the phenotypic and functional differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
0
30
0
1
Order By: Relevance
“…Despite that, these cells are able to express cytokines, chemokines and growth factors involved in tumorigenesis and therapeutics resistance profile (reviewed by M. ). Barrera- Rodríguez and Fuentes (2015) suggested that INER-37 and INER-51 lung cancer spheroids are more resistance toward etoposide, teniposide, doxorubicin, or camptothecin when compared with 2D cell cultures, a result that was associated to the quiescent cell subpopulation found in the spheroids. In a different study, Gong et al (2015) analyzed the cell cycle of MCF-7 breast cancer cells cultured in monolayer or spheroids through flow cytometry.…”
Section: Cell-cycle Arrestmentioning
confidence: 99%
“…Despite that, these cells are able to express cytokines, chemokines and growth factors involved in tumorigenesis and therapeutics resistance profile (reviewed by M. ). Barrera- Rodríguez and Fuentes (2015) suggested that INER-37 and INER-51 lung cancer spheroids are more resistance toward etoposide, teniposide, doxorubicin, or camptothecin when compared with 2D cell cultures, a result that was associated to the quiescent cell subpopulation found in the spheroids. In a different study, Gong et al (2015) analyzed the cell cycle of MCF-7 breast cancer cells cultured in monolayer or spheroids through flow cytometry.…”
Section: Cell-cycle Arrestmentioning
confidence: 99%
“…In respect to conventional 2D cultures, the added dimensionality enables the formation of large and variable tumour spheroids similar in morphology to those observed in vitro . Additionally, spheroids in 3D displayed a better resistance to drug treatments (Barrera‐Rodriguez and Morales Fuentes, ). Synthetic scaffolds can be produced with predefined shape, porosity and stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Activations of mechanisms related to drug efflux in spheroid can be responsible for increased resistance to the drugs. In 2015, Rodriguez et al showed an increased expression of MDR-1 and P-glycoprotein in spheroids of INER-37 human NSCLC cell line compared to 2D culture likely responsible for increased drug resistance [58]. Several studies have indicated CSC enrichment in spheroids as possible explanation for drug resistance and metastasis [59,60].…”
Section: Lung Cancer -Strategies For Diagnosis and Treatmentmentioning
confidence: 99%